2022
DOI: 10.1111/jdi.13797
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multi‐metal exposure on the risk of diabetes mellitus among people aged 40–75 years in rural areas in southwest China

Abstract: Aims/Introduction: Metals play an important role in diabetes mellitus. This crosssectional study aimed to evaluate the overall, individual and interactive effects of multimetal exposure on the prevalence of diabetes mellitus, impaired fasting glucose (IFG) rate and fasting blood glucose (FBG) levels. Materials and Methods:The FBG levels of a study population from a cadmium (Cd)polluted area (n = 250) and an unpolluted area (n = 204), and the metal levels, including magnesium, calcium (Ca), iron (Fe), zinc (Zn)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…The concentrations of serum Mg (median/mean: 0.95 mmol/L) in the present study were slightly higher than those described in NHANES I study in the U.S. (median: 0.85 mmol/L) [ 35 ], and from the EPIC-Norfolk cohort study in the UK (males: 0.82 mmol/L; females: 0.80 mmol/L) [ 36 ], while were slightly lower than that reported in the rural areas of the southwest of China (median: 1.07 mmol/L) [ 37 ]. The difference in serum Mg levels among these regions may be attributed to the inclusion of age limit, dietary preference, drinking water, and race specificity [ 35 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 89%
“…The concentrations of serum Mg (median/mean: 0.95 mmol/L) in the present study were slightly higher than those described in NHANES I study in the U.S. (median: 0.85 mmol/L) [ 35 ], and from the EPIC-Norfolk cohort study in the UK (males: 0.82 mmol/L; females: 0.80 mmol/L) [ 36 ], while were slightly lower than that reported in the rural areas of the southwest of China (median: 1.07 mmol/L) [ 37 ]. The difference in serum Mg levels among these regions may be attributed to the inclusion of age limit, dietary preference, drinking water, and race specificity [ 35 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 89%
“…Similar results were obtained in the participants of this study, while trend tests showed that participants' blood lead levels increased with age and that this trend was more pronounced in participants with HBcAb (+). Lead exposure could increase the prevalence of metabolic disorders, and the risk of metabolic disorders increases with age ( 27 ). We believe that metabolic diseases might alter the mechanisms by which lead is metabolized in the body, which could also explain the higher blood lead levels in the older participants.…”
Section: Discussionmentioning
confidence: 99%
“…There is proof that exposure to specific metals, such as arsenic (As), mercury (Hg), cadmium (Cd), and lead (Pb), causes T2D. This exposure can occur through contaminated food and water, inhalation of polluted air, and occupational exposure [ 99 , 118 , 119 ]. As, Cd, Hg, and Pb are among the hazardous metals that can cause oxidative stress by boosting the generation of reactive oxygen species (ROS), which include nitric oxide, hydrogen peroxide, and superoxide radicals.…”
Section: Factors Leading To Development Of T2dmentioning
confidence: 99%